Sequence-specific DNA purification by triplex affinity capture. - Ito, T (1992)
A DNA isolation procedure was developed by using triple-helix formation and magnetic separation. In this procedure, target DNA is captured by a biotinylated oligonucleotide via intermolecular triplex formation, bound to streptavidin-coated magnetic beads, and recovered in double-stranded form by elution with a mild alkaline buffer that destabilizes the triple helix. The effectiveness of the procedure was demonstrated by a model experiment with an artificially reconstructed library and, also, by the isolation of (dT-dC)n.(dG-dA)n dinucleotide repeats from a human genomic library. This procedure provides a prototype for other triplex-mediated DNA isolation technologies.